2016
DOI: 10.1002/jcad.12105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wellness‐Focused Supervision on Mental Health Counseling Practicum Students

Abstract: Professional counseling organizations tout the importance of wellness for counselors and counselors‐in‐training. The authors used a wellness‐focused supervision model with mental health practicum students to assess the model's degree of treatment effect at improving students' wellness over the course of the semester. Participants' demographics included three women, one man, three European Americans, and one Latino/a. Single‐case design results revealed that ongoing wellness‐focused interventions are helpful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…Inversely, minimal exposure to the intervention resulted in extended influence of secondary traumatic stress characteristics. Similar results were detected by Meany‐Walen et al (), who concluded that CIT engagement in the WELMS was a protective factor for the experiences of increased risk for psychological stress during internship.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Inversely, minimal exposure to the intervention resulted in extended influence of secondary traumatic stress characteristics. Similar results were detected by Meany‐Walen et al (), who concluded that CIT engagement in the WELMS was a protective factor for the experiences of increased risk for psychological stress during internship.…”
Section: Discussionsupporting
confidence: 87%
“…Several recommendations for use of the WELMS with counseling students are available from the findings within the context of professional literature. When we consider that CITs are required to learn and demonstrate skills necessary for maintaining their ProQOL, there is a body of evidence indicating the utility of integrating proactive approaches to develop career‐sustaining behaviors during the practicum and internship experiences (Lenz et al, ; Meany‐Walen et al, ; Ohrt et al, ). Lawson () found that in the absence of these skills, counselors are vulnerable to experiencing burnout and decreased clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have proposed strategies to incorporate wellness models in counselor training and supervision (Lenz et al, 2012; Meaney‐Walen et al, 2016; Ohrt et al, 2015; Wolf et al, 2014). Some of these models are derived from the indivisible self model of wellness (IS‐Wel; Myers & Sweeney, 2005), which emphasizes holism and purpose as crucial to understanding individuals and how they engage with the world.…”
Section: Wellness Promotion In Counselor Educationmentioning
confidence: 99%
“…Furthermore, a higher sense of burnout predicts, among other things, school counselors’ job dissatisfaction and decreased delivery of direct student services (Mullen et al, 2018; Mullen & Gutierrez, 2016). Authors have highlighted self-care (Lawson, 2007) and protective factors (Young & Lambie, 2007) to decrease the impact of stress caused by working as a school counselor, and other researchers have examined training interventions to prepare new school counselors to effectively maintain well-being while they start their career (Meany-Walen et al, 2016; Ohrt et al, 2015).…”
mentioning
confidence: 99%